1991
DOI: 10.1001/archsurg.1991.01410360025005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Submicroscopic Lymph Node Metastases in Patients With Melanoma

Abstract: A cell culture technique was developed to investigate submicroscopic lymph node metastases in patients with stage 1 or 2 malignant melanoma. Lymph nodes were isolated from standard dissections and bivalved. Half of the node was evaluated by routine histopathologic examination, while the other half was processed and placed into tissue culture. Three hundred twenty-three lymph nodes were collected from 41 patients. The cell culture technique identified 155 of 323 lymph nodes containing micrometastases, while onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…It means only that to the extent the node was examined, the pathologist did not observe cancer cells. More aggressive techniques to identify cancer cells-for example, serial sections, 22 immunohistochemistry, 23 reverse-transcription polymerase chain reaction, 24 and tissue culture 25 -can result in detection of additional cancer cells in nodes that previously were considered free of cancer. The threshold number of cancer cells necessary to initiate clonogenic growth in a lymph node is simply unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It means only that to the extent the node was examined, the pathologist did not observe cancer cells. More aggressive techniques to identify cancer cells-for example, serial sections, 22 immunohistochemistry, 23 reverse-transcription polymerase chain reaction, 24 and tissue culture 25 -can result in detection of additional cancer cells in nodes that previously were considered free of cancer. The threshold number of cancer cells necessary to initiate clonogenic growth in a lymph node is simply unknown.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Neither of these studies reported clinical follow-up, and currently neither of these techniques is applicable to routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…The human tyrosinase gene is reportedly expressed only in Schwann cells, normal melanocytes, and malignant melanoma cells. 34 After purification of total cellular RNA, complementary DNA (cDNA) fragments of tyrosinase mRNA are made by a RT step in the presence of a specific primer (HTYR2). Two rounds of PCR using nested primer pairs (HTYR1/HTYR2 and HTYR3/HTYR4) then amplify the tyrosinase cDNA.…”
Section: Htyr2mentioning
confidence: 99%